2015
DOI: 10.1007/7081_2015_173
|View full text |Cite
|
Sign up to set email alerts
|

Guanidine Metal Complexes for Bioinorganic Chemistry and Polymerisation Catalysis

Abstract: Guanidines are highly useful ligands which have conquered coordination chemistry within the last 20 years. Their CN 3 moiety allows multiple substitution patterns which enables tailoring them to a large variety of applications, ranging from bioinorganic coordination chemistry via medicinal chemistry to polymerisation catalysis. In bioinorganic chemistry, guanidines gave important stimuli in the modelling of copper type 1, 2 and 3 enzymes. This review provides with a comprehensive overview on complexes which ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 192 publications
0
20
0
Order By: Relevance
“…This is related to the strong donation of N gua donor atoms to the Cu II centres [see natural bond orbital (NBO) calculations]: the C gua –N imine,gua bond shifts electron density to the N gua donor, which results in an elongation of the C gua –N imine,gua bond and a shortening of the C gua –N amine,gua bond . In all of these complexes, a twist within the guanidine moiety is observed, and this is characteristic of peralkylated guanidine ligands . This twist is a result of the competition between the electronic effects of the intra‐guanidine conjugation and the evasion of the alkyl substituents.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is related to the strong donation of N gua donor atoms to the Cu II centres [see natural bond orbital (NBO) calculations]: the C gua –N imine,gua bond shifts electron density to the N gua donor, which results in an elongation of the C gua –N imine,gua bond and a shortening of the C gua –N amine,gua bond . In all of these complexes, a twist within the guanidine moiety is observed, and this is characteristic of peralkylated guanidine ligands . This twist is a result of the competition between the electronic effects of the intra‐guanidine conjugation and the evasion of the alkyl substituents.…”
Section: Resultsmentioning
confidence: 99%
“…This twist is a result of the competition between the electronic effects of the intra‐guanidine conjugation and the evasion of the alkyl substituents. The angles between the C gua N 3 and N amine C 3 planes lie in the range 7.7–11.4° and are smaller than those in the corresponding TMGqu Cu complexes because the twist in DMEG complexes is hindered by the rigid ethylene bridge between the amine groups of the guanidine moiety , . In C5 , one triflate anion interacts weakly with the Cu II centre [2.375(3) and 2.786(4) Å for the two molecules in the asymmetric unit].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[34,35] The preferential stabilisation of O core species in the presence of bidentate guanidine ligands is due to their excellent σand πdonor abilities. [29,[36][37][38] In the context of tetradentate ligands, the steric demands and excellent donor properties of the guanidine groups in the tris(guanidine) ligand TMG 3 tren ( Figure 1) have been successfully used in the last years to stabilise a superoxido end-on monocopper species and to study the subsequent chemistry of this exceptional complex. [39][40][41][42] Some of us previouslyinvestigatedthereactivityofthecopper(I)complexwith 2-[3-(dimethylamino)propyl]-1,1,3,3-tetramethylguanidine (TMGdmap) as ligand towards dioxygen in comparison with copper(I) complexes of the ligands 1,3-bis(N,N,N′,N′-tetramethylguanidino)propane (btmgp) and teramethylpropylenediamine (TMPD).…”
Section: Introductionmentioning
confidence: 99%
“…7 It was shown that bisIJguanidine) ligands are strong N-donors and stabilise high metal oxidation states. 8,9 BisIJguanidine) li-gands represent a ligand class which is intensively investigated for use in biomimetic coordination chemistry. 10,11 Libraries of ligands with different attributes have been synthesised and studied.…”
Section: Introductionmentioning
confidence: 99%